2021
DOI: 10.3389/fendo.2021.684018
|View full text |Cite
|
Sign up to set email alerts
|

Tunisian Maturity-Onset Diabetes of the Young: A Short Review and a New Molecular and Clinical Investigation

Abstract: Introduction/AimsMaturity-Onset Diabetes of the Young (MODY) is a monogenic non-autoimmune diabetes with 14 different genetic forms. MODY-related mutations are rarely found in the Tunisian population. Here, we explored MODY related genes sequences among seventeen unrelated Tunisian probands qualifying the MODY clinical criteria.Materials and MethodsThe GCK and HNF1A genes were systematically analyzed by direct sequencing in all probands. Then, clinical exome sequencing of 4,813 genes was performed on three unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…16 Sudan 17 and Kenya. 18 For MODY, four papers were identified from Tunisia [19][20][21][22] and one each from Morocco, 23 South Africa 24 and Sudan 25 that had evaluated the prevalence of MODY in those countries (Figure 2). The map representation of the studies based on the countries from which they were conducted has been shown in Figures 3a and 3b.…”
Section: Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Sudan 17 and Kenya. 18 For MODY, four papers were identified from Tunisia [19][20][21][22] and one each from Morocco, 23 South Africa 24 and Sudan 25 that had evaluated the prevalence of MODY in those countries (Figure 2). The map representation of the studies based on the countries from which they were conducted has been shown in Figures 3a and 3b.…”
Section: Mappingmentioning
confidence: 99%
“…The current diabetes treatment was also recorded for some of the studies. [22][23][24] Clinical parameters can be used as prognostic markers for disease outcome. Thus, analysis of these parameters is important for understanding disease trajectory.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…All variants with coverage greater than 20 were analyzed. A special focus was given to a list of 133 genes related to diabetes, glucose metabolism, and the insulin pathway [15]. In addition, the functional impacts of the selected coding variants were predicted using the following tools: Sorting Intolerant From Tolerant (SIFT) [16], Protein Variation Effect Analyzer (PROVEAN) [17], and Polymorphism Phenotyping v2 (PolyPhen-2) [18].…”
Section: Cesmentioning
confidence: 99%